2015
DOI: 10.1016/j.ejmech.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Isatin-pyrazole benzenesulfonamide hybrids potently inhibit tumor-associated carbonic anhydrase isoforms IX and XII

Abstract: a b s t r a c tNew series of benzenesulfonamide derivatives incorporating pyrazole and isatin moieties were prepared using celecoxib as lead molecule. Biological evaluation of the target compounds was performed against the metalloenzyme carbonic anhydrase (CA, EC 4.2.1.1) and more precisely against the human isoforms hCA I, II (cytosolic), IX and XII (transmembrane, tumor-associated enzymes). Most of the tested compounds efficiently inhibited hCA I, II and IX, with K I s of 2.5e102 nM, being more effective tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…36) showed good carbonic anhydrases inhibition to the cell lines hCA IX (K i ¼ 15.7 and 7.4 nM, respectively) and hCA XII (K i ¼ 3.7 and 5.4 nM, respectively). The SAR studies suggested that the presence of EWGs (NO 2 ) on the phenyl ring to increased the activity and sulphonamide played a major role in the enhancing the CA activity [231]. In 2014, Tiangong and co-workers developed compound (307 and 308) (Fig.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…36) showed good carbonic anhydrases inhibition to the cell lines hCA IX (K i ¼ 15.7 and 7.4 nM, respectively) and hCA XII (K i ¼ 3.7 and 5.4 nM, respectively). The SAR studies suggested that the presence of EWGs (NO 2 ) on the phenyl ring to increased the activity and sulphonamide played a major role in the enhancing the CA activity [231]. In 2014, Tiangong and co-workers developed compound (307 and 308) (Fig.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Ibrahim et al [59] was responsible for the synthesis of different isatin-pyrazole benzenesulfonamide hybrids 39 as inhibitors of tumor-associated carbonic anhydrases M A N U S C R I P T…”
Section: Figure 25mentioning
confidence: 99%
“…They are shown to act as caspases‐3 and ‐7 inhibitors, antitubercular, [ ][ ] antileukemia and antimicrobial agents [ ][ ] ( Figure ). The analysis of works on design and target synthesis of biologically active isatin‐3‐acylhydrazones showed a strong dependence of the type and level of activity on the structure of the functional substituent in the hydrazone fragment . However, despite the large number of such studies, the problem of solubility of the target compounds in biorelevant solvents remains urgent.…”
Section: Introductionmentioning
confidence: 99%